THE ROLE OF ORGANIZATIONAL CITIZEN BEHAVIOR ON EMPLOYEE PERFORMANCE : A CASE STUDY COCA COLA OFFICIAL DISTRIBUTOR - Lala Setiany Wee; Helena Sidharta; Eric Harianto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to provide empirical evidence and elucidate the influence of organizational climate, Transformational Leadership, and job satisfaction on Organizational Citizenship Behavior (OCB) and how OCB impacts the performance of employees at PT Mitra Sukses Sejahtera, an Official Distributor of Coca-Cola. This research utilizes organizational climate, job satisfaction, and Transformational Leadership as independent variables, OCB as a mediating variable, and employee performance as a dependent variable. A saturation sampling method was employed, with 110 respondents from Coca Cola Official Distributor PT Mitra Sukses Sejahtera's employees . Data was analyzed using the Structural Equation Modeling - Partial Least Square (SEM-PLS) method via SEM-PLS version 4.0 software. The findings indicate that organizational climate, job satisfaction, and Transformational Leadership have a significant positive relationship with OCB. Furthermore, OCB exhibits a positive and significant relationship with the performance of employees at PT Mitra Sukses Sejahtera. Therefore, this study provides valuable insights into how these factors influence OCB and employee performance in an organizational context.